2020
DOI: 10.1111/and.13756
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of seminal YKL‐40 in infertile men with varicocele

Abstract: Varicocele, a dilation of pampiniform plexus, has a common association in male factor infertility (Alsaikhan, Alrabeeah, Delouya, & Zini, 2016). Several studies showed that varicocele harms spermatogenesis, testicular volume, semen parameters, sperm functions, fertilisation, implantation and the embryo outcome (Kimura & Nagao, 2014; Çayan, Orhan, Akbay, & Kadıoğlu, 2019). In infertile men with varicocele, impairment of the venous drainage is accompanied by stasis, bilateral testicular ischemia, tissue hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Therefore, increased seminal Cys C in infertile OAT men with varicocele could be explained on the background of increased seminal features of apoptosis, oxidative stress as well autophagy in varicocele‐associated cases (Abd El Rahman et al., 2020; Dieamant et al., 2017; Foroozan‐Broojeni et al., 2019; Ghandehari‐Alavijeh et al., 2019; Mikhael et al., 2018; Zalata et al., 2011). Besides, the current study showed significant decreases in the seminal levels of Cys C after varicocelectomy concomitant with the improved semen parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increased seminal Cys C in infertile OAT men with varicocele could be explained on the background of increased seminal features of apoptosis, oxidative stress as well autophagy in varicocele‐associated cases (Abd El Rahman et al., 2020; Dieamant et al., 2017; Foroozan‐Broojeni et al., 2019; Ghandehari‐Alavijeh et al., 2019; Mikhael et al., 2018; Zalata et al., 2011). Besides, the current study showed significant decreases in the seminal levels of Cys C after varicocelectomy concomitant with the improved semen parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, in their systemic review, Asafu-Adjei et al (2020) demonstrated significant improvement in the mean sperm concentration after varicocelectomy in men with all varicocele grades where the magnitude of improvement was directly related to varicocele grade. As well, several studies linked increased varicocele grade with seminal apoptotic and oxidative stress harmful effects(Ashrafzade et al, 2020;Mostafa et al, 2020;Vivas-Acevedo et al, 2010).…”
mentioning
confidence: 99%
“…It has been reported that varicocoelectomy induces decreased seminal YKL‐40 levels and improves semen parameters. There is a negative correlation of seminal YKL‐40 levels with sperm count, total motility and normal morphology indicating YKL40 could be a useful biomarker for the varicocoele 191 …”
Section: Effect Of Varicocoele On Seminal Plasma Milieumentioning
confidence: 99%
“…There is a negative correlation of seminal YKL-40 levels with sperm count, total motility and normal morphology indicating YKL40 could be a useful biomarker for the varicocoele. 191 miRNAs are powerful regulators of key cellular processes such as differentiation, proliferation, and apoptosis by affecting protein translation. Seminal plasma micro-RNAs (Let-7 and miR-19b) may be potential biomarkers for spermatogenic status as they are released from germinal cells and their expression is largely stable.…”
Section: Effect Of Varicocoele On Seminal Plasma Milieumentioning
confidence: 99%